The Role of Platelet Indices in Predicting Short-Term Mortality in Elderly Patients with Pulmonary Embolism - Serdar Özdemir; Abdullah Algın (Journal of Contemporary Medicine, 2021)
Objective: This study aimed to investigate the role of platelet count, mean platelet volume (MPV), plateletcrit, platelet distribution width (PDW), platelet mass index (PMI), and MPV-to-platelet count ratio (MPR) in predicting short-term mortality in patients aged 65 and over with pulmonary embolism. Methods: This retrospective, observational, cohort study included corrected pulmonary embolism patients. Demographics, clinical characteristics, and platelet indices and the data of all-cause mortality within 30 days after admission were noted. The receiver operating characteristic curve analysis and multivariate analysis was performed to determine the discriminative ability of the scores. Results: A final analysis of 128 patients was performed. The mortality rate was 21.8%. There was no significant relationship in the multivariate analysis between mortality and platelet indices (Mann-Whitney U test). Area under curves of neutrophil-to-lymphocyte ratio, PMI, MPR, plateletcrit, platelet count, and MPV are 0.501, 0.640, 0.626, 0.642, 0.633, and 0.532, respectively. Conclusion As a conclusion based on results of our simple, platelet indices could not predict short-term mortality in elderly patients with pulmonary embolism.